هندسة المسافات الاجتماعية في الجيوب القروية داخل المدن - مناصرية, ميمونة (Changement Social, 2018)
المكان هو الفراغ المشغول من قبل الأفراد والجماعات، وعلى قدر تنوع الأمكنة المشغولة يتشكل سلم المعايير والقيم الاجتماعية - لكل مكان-  وتتنوع مفرداته، وتتفاوت فيه نسب القداسة والتبجيل لمختلف المعاني والرموز. وتشكل الجيوب القروية داخل المدن مجالا متميزا يختلف عن المدينة وعن الريف وعن القرية أيضا، حيث يشكله معمار مديني وتسوده سلوكات قروية مما يرسم للتناقض لوحات متعددة، تبدو واضحة من خلال الظواهر الاجتماعية والأفعال اليومية والسلوكات الفردية وكذا مختلف العلاقات الاجتماعية . وكثيرا ما تظهر المسافة بين الأفراد أمرا مسلما به في ظل معايير اجتماعية متفق عليها، لكن الاعتراف بوجود فكرة المسافة بين الأفراد، كأمر قابل للدراسة يحتاج إلى كثير من الإدراك الحسي والحدسي على السواء.... إذ يشكل الإيماء والإيحاء والتحية والمصافحة وكل أشكال التقاء الوجوه ....شكلا من أشكال التواصل بين الأفراد، فيما يتم رسم المسافة خلال هذا التواصل على المستوى الإدراكي والحدسي بشيء من التفاوت حسب الموقف الاجتماعي المتأثر أساسا بمختلف القيم الدينية والعادات والتقاليد وأعراف الناس. وتتعرض هذه المقالة إلى أشكال المسافة بين الأفراد في الجيوب القروية داخل المدن. Place is the vacuum occupied by individuals and groups, and the diversity of places occupiedforms the ladder of standards and social values - each place - and variedvocabulary, and vary proportions of holiness and reverence for the variousmeanings and symbols. The village enclaves within the citiesconstitute a distinct area thatdiffersfrom the city, from the countryside and from the village as well. It isaurban architecture and has rural behavior. This contrastswithmanypaintings, which are evidentthrough social phenomena, daily actions, individualbehaviors and various social relations. The distance betweenindividualsisoftenrecognized as an accepted social standard, but recognizing the idea of distance betweenindividuals as a matter of studyrequires a lot of sensory and intuitive perception. It is the gesture, inspiration, greeting, the forms of convergence of faces ... aform of communication betweenindividuals, while the distance isdrawnduringthis communication at the level of perception and intuition withsomedisparitydepending on the social situation affectedmainlydifferentreligious values and customs and traditions of people. This article deals with the forms of distance betweenindividuals in rural enclaves withincities..